2008
DOI: 10.1097/cad.0b013e3282f3fd2e
|View full text |Cite
|
Sign up to set email alerts
|

Oral bioavailability of a novel paclitaxel formulation (Genetaxyl) administered with cyclosporin A in cancer patients

Abstract: The formulation excipient Cremophor EL (CrEL) is known to limit absorption of oral paclitaxel given together with cyclosporin A (CsA). We hypothesized that the use of oral Genetaxyl, a paclitaxel formulation containing only 20% CrEL would have an improved oral bioavailability. Cohorts of 6 patients were treated with oral Genetaxyl at a dose of 60, 120, or 180 mg/m 2 and 10 mg/kg of oral CsA in cycle 1. In cycle 2, patients received intravenous (i.v.) Genetaxyl (175 mg/m 2 , 3-hour infusion). Three additional p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
21
0

Year Published

2009
2009
2022
2022

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 25 publications
(21 citation statements)
references
References 28 publications
0
21
0
Order By: Relevance
“…Unfortunately, standard LNCs and LNCs with chitosan presented no beneficial effect in reducing interindividual variability (variation of 69% in AUC for both LNCs vs. 49% for Ptx commercial formulation). After oral administration of a Taxol generic or a Ptx formulation with less Cremophor EL, associated with cyclosporin A, a high interindividual variability was observed in human (coefficient of variation in AUC varied from 14.5 to 63.9% according to the dose) [41]. On the opposite, PEG 2000 -amino postinserted LNCs present an effect on the reduction in interindividual variability (variation of 36% in AUC).…”
Section: Discussionmentioning
confidence: 97%
“…Unfortunately, standard LNCs and LNCs with chitosan presented no beneficial effect in reducing interindividual variability (variation of 69% in AUC for both LNCs vs. 49% for Ptx commercial formulation). After oral administration of a Taxol generic or a Ptx formulation with less Cremophor EL, associated with cyclosporin A, a high interindividual variability was observed in human (coefficient of variation in AUC varied from 14.5 to 63.9% according to the dose) [41]. On the opposite, PEG 2000 -amino postinserted LNCs present an effect on the reduction in interindividual variability (variation of 36% in AUC).…”
Section: Discussionmentioning
confidence: 97%
“…A number of clinical trials have been reported in which orally bioavailable chemotherapeutic drugs such as cyclophosphamide, methotrexate, and capecitabine were given daily to treat patients with metastatic breast cancer (39,40). Several new formulations to enhance the oral bioavailability of paclitaxel and oral paclitaxel analogues have been invented (41)(42)(43).…”
Section: Discussionmentioning
confidence: 99%
“…The spectrum of effects that has been associated with changes in formulation includes variable impact of food on drug absorption [10], altered bioavailability [11,12] including altered drug absorption [13,14], and even potential changes in the delivery to tumor target site [12,15]. Initial trials in the axitinib clinical development program were conducted using tablets containing crystal polymorph axitinib Form IV FCIR of axitinib drug substance [1,[3][4][5][16][17][18].…”
Section: Discussionmentioning
confidence: 99%